Pendidikan dan Pelatihan Jurnalistik Online bagi Kalangan Remaja di Kabupaten Purwakarta - Faisal Muzzammil; Elsa Dwi Pebrianti; Qonnita Jannati; Neng Azizah; Dewi Nurhasanah; Fajar Ariefinto (Arsil Media, 2024)
This Community Service Activity (CSA) is motivated by the need to equip teenagers in Purwakarta Regency with the knowledge and skills of online journalism which is currently developing in the current digital era. Based on this background, CSA were carried out in the form of online journalism education and activities for groups in Purwakarta Regency. This CSA has two objectives, namely: (1) Providing basic education and knowledge to participants about Online Journalism; (2) Providing practical training for participants in creating Online Journalism products. This CSA is carried out using the Service Learning method. Significantly, this CSA has been carried out well and has achieved maximum results in the following two points: (1) Participants were able to recognize and understand online journalism from its inception to various online media as a real form of online journalism; (2) Participants can write news and articles that are suitable for publication in online media or uploaded to social media.